Initiating gay relationships in the Philippines a history of mediatization and place-making - Solis, Randy Jay C. (2021)
Access online through this link: https://www.plarideljournal.org/article/initiating-gay-relationships-in-the-philippines-a-history-of-mediatization-and-place-making
Keywords: Gay male relationships; Gay male dating; Online dating mobile apps; Communication and technology